2020
DOI: 10.1002/ldr.3606
|View full text |Cite
|
Sign up to set email alerts
|

Grazing significantly increases root shoot ratio but decreases soil organic carbon in Qinghai‐Tibetan Plateau grasslands: A hierarchical meta‐analysis

Abstract: The Qinghai-Tibetan Plateau (QTP) is the most expansive area of alpine grasslands worldwide, which have been grazed for thousands of years. Distinct environmental conditions render QTP grasslands vulnerable to disturbances. Intensified grazing in the area has led to its degradation in recent decades. However, the effects of grazing on grassland production, soil carbon, and nitrogen contents, their relationships and the factors influencing the grasslands of QTP have yet to be determined. In this study, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 79 publications
1
40
1
4
Order By: Relevance
“…Soil total carbon is a key factor affected by grazing (Hu et al 2016;Mcsherry and Ritchie 2013) which is the most frequently used trait in soil quality calculation (Askari and Holden 2014). The reduced carbon inputs from above-and belowground biomass in the degraded grassland may be the main drivers for the lower content of total carbon (Shen et al 2020;Wilson et al 2018;Yan et al 2020). In the meadow steppe, we also found that soil carbon stock was lower than the TG (Fig.…”
Section: Effects Of Grassland Degradation On Soil Qualitymentioning
confidence: 66%
See 1 more Smart Citation
“…Soil total carbon is a key factor affected by grazing (Hu et al 2016;Mcsherry and Ritchie 2013) which is the most frequently used trait in soil quality calculation (Askari and Holden 2014). The reduced carbon inputs from above-and belowground biomass in the degraded grassland may be the main drivers for the lower content of total carbon (Shen et al 2020;Wilson et al 2018;Yan et al 2020). In the meadow steppe, we also found that soil carbon stock was lower than the TG (Fig.…”
Section: Effects Of Grassland Degradation On Soil Qualitymentioning
confidence: 66%
“…Researches in grassland have shown that management intensification has an adverse impact on soil and plant characteristics (Askari and Holden 2014). For example, overgrazing not only reduces the biomass of palatable species (Gaitán et al 2018) but also changes root shoot ratio and soil bulk density (Hendricks et al 2005;Yan et al 2020), which in turn leads to a reduction in soil carbon and nitrogen pools (Hu et al 2016;Yan et al 2020). Thus, soil quality index is the summarizing of these interdependent properties by choosing the best representative indicators which can comprehensively evaluate the effects of grassland degradation on soil quality and ecosystem function (Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the meta-analysis based on 140 studies over a China scale performed by Hao and He (2019), our meta-analysis indicated that the effects of grazing on the AGB of the Tibetan Plateau grassland was greater than in China scale, but the opposite results were shown for BGB. It is shown that grazing leads to more BGB allocation, which is conducive to the survival of high-altitude plants in an environment with low temperature and limited nutrients (Yan et al 2020).…”
Section: Compared With the Findings Of Grazing Studies In Other Regionsmentioning
confidence: 99%
“…Yan et al (2013) found that, compared to the global average value, grazing had a greater negative effect on grassland total biomass in China. The recent meta-analyses of Yan et al (2020) and Liu et al (2021)showed that heavy grazing significantly decreased the biomass and soil total N. However, a synthesis of the effect of grazing on alpine grassland on the Tibetan Plateau is still lacking, which indicated that the general response of alpine grassland on the Tibetan Plateau to grazing remains unclear. Given these studies, it is necessary to integrate the available data to analyze how grazing affects alpine grassland.…”
Section: Introductionmentioning
confidence: 99%
“…Plant biomass is the main input of organic carbon into the soil (Shipley and Parent, 1991). However, a not so frequently considered factor is plant litter quality, which can determine decomposition rates and patterns and hence soil carbon sequestration (Ottoy et al, 2017;Yan et al, 2018Yan et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%